2013
DOI: 10.3109/13814788.2013.805198
|View full text |Cite
|
Sign up to set email alerts
|

An unexpected temporary suppression of lactation after a local corticosteroid injection for tenosynovitis

Abstract: Local injection of MPA reversibly suppressed lactation in a young woman for a period of 24-48 h. Doctors using injectable GCS in lactating women should apprise patients of this possibility. Mothers can take precautions like expressing and storing enough breast milk to cover this period prior to receiving these injections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…This effect of GC on lactose synthesis, including the effect of exogenous GC, can be revealed in different models and states. For example, lactating humans who received an injection of exogenous GC for musculoskeletal pain had complete or near complete suppression of milk production within one day [98,99]. In the same way, synthetic GC administered to lactating cows reduced milk lactose concentration from 46 to 43 mg/ml within 24 h of treatment, concomitant with a decrease in milk yield of approximately 10 kg/d [100].…”
Section: Glucocorticoids (Gc)mentioning
confidence: 99%
“…This effect of GC on lactose synthesis, including the effect of exogenous GC, can be revealed in different models and states. For example, lactating humans who received an injection of exogenous GC for musculoskeletal pain had complete or near complete suppression of milk production within one day [98,99]. In the same way, synthetic GC administered to lactating cows reduced milk lactose concentration from 46 to 43 mg/ml within 24 h of treatment, concomitant with a decrease in milk yield of approximately 10 kg/d [100].…”
Section: Glucocorticoids (Gc)mentioning
confidence: 99%
“…However, the use of glucocorticoid can cause a temporary decrease of milk production in nursing mothers. Babwah et al [ 15 ] reported a case of temporary suppression of lactation with a nursing mother who was given local corticosteroid for treatment of tenosynovitis. In this case, we first performed a diagnostic II/IH nerve block with ropivacaine and dexamethasone.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is negligible gut absorption from the baby, and so there is no significant risk of hypothalamus-pituitary-adrenal axis suppression. There are, however, documented cases of lactation suppression secondary to triamcinolone injection [17,18]. Corticosteroids are a substrate of the enzyme CYP3A4, which is targeted and blocked by many anti-retrovirals (ritonavir), anti-fungals, calcium-channel blockers (diltiazem), and the oral contraceptive pill, to name a few.…”
Section: Ia Corticosteroids—mechanism Of Actions and Pharmacokineticsmentioning
confidence: 99%